The Sanitary Condition of Food Establishments and Health Status and Personal Hygiene among Food Handlers in a Rural Area of Western Maharashtra, India - Deshpande, Jayant D; Phalke, Deepak B (Asian Journal of Medical Sciences, 2013)
Background: Foodborne disease occurs in mass catering establishment that is not complying with sanitary and hygienic food handling and preparation. Objective: Objective of the present study was to explore the status of sanitary condition of food establishments and to assess hygienic practices among food handlers. Material and Method: A cross-sectional study design was used to assess the sanitary condition of food establishments and personal hygiene of food handlers. Data was collected with the help of structured and pre-tested questionnaires. The questionnaire also allowed the interviewers to record their observations. All the data obtained was entered into Microsoft Excel and analyzed using the software StatistiXL version 1.8. Result: Separate kitchen and Onsite solid waste storage containers/receptacles were available in 4(16%) establishments. Provision for heating devices for cooked food was available in 5(20%) establishments. Wash basin present with soap were available in 10 (40%) of the food establishments. Sweeping and washing floor with water and disinfectant was done in 8(32%) food establishments. Male and female food handlers’ have equal percentage of morbidity and this difference was not statistically significant (χ2=0.0329, p=0.84), but anaemia was significantly higher among female food handlers (χ2=6.30, p=0.01). Poor hygienic practices were significantly associated with presence of infectious diseases like ARI, diarrhoea, dysentery and skin infections. (χ2=5.71, p=0.017). Conclusion: Food establishments in the study area were found to have poor sanitation and were not maintained well. The health status and the level of personal hygiene of the food handlers in the eating establishments were found to be unsatisfactory. There is need of enforcement of sanitary provisions and educating the food handlers about personal hygiene. DOI: http://dx.doi.org/10.3126/ajms.v4i2.7895 Asian Journal of Medical Sciences 4(2013) 23-29